1980
DOI: 10.4141/cjss80-027
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF VESICULAR-ARBUSCULAR MYCORRHIZA ON 14C AND 15N DISTRIBUTION IN NODULATED FABABEANS

Abstract: PrNo, P. C. ,rNo Peul, E. A. 1980

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
1
8

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 19 publications
10
62
1
8
Order By: Relevance
“…Some earlier studies report an increase in respiration in roots colonised by AMF (Pang and Paul 1980;Peng et al 1993), but others do not (Silsbury et al 1983). Size asymmetry between mycorrhizal and non-mycorrhizal plants is an important factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some earlier studies report an increase in respiration in roots colonised by AMF (Pang and Paul 1980;Peng et al 1993), but others do not (Silsbury et al 1983). Size asymmetry between mycorrhizal and non-mycorrhizal plants is an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Allocation of C to AMF may vary with stage of plant development (Mortimer et al 2005). Although some studies have shown that colonisation of roots by AMF can increase belowground respiration (Pang and Paul 1980;Peng et al 1993), others have suggested otherwise (Silsbury et al 1983). Reasons for such differences remain unknown, although size differences between mycorrhizal and non-mycorrhizal plants are likely an important factor in determining total belowground respiration (Langley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also thought that the plant-Rhizobium system benefits from the presence of arbuscular mycorrhizae because the mycorrhizae correct not only P deficiency but also any nutrient deficiency in the plant that might be limiting to the Rhizobium (Pacovsky 1986 ;O'Hara et al 1988). Increased mineral nutrient levels in the plant would not only benefit Rhizobium directly, but would also lead to increased photosynthesis, making a greater proportion of photosynthates available to the Rhizobium nodules (Pang and Paul 1980 ;Harris et al 1985). This paper is concerned with the interactions between Rhizobium leguminosarum and an antibiotic (DAPG) and non-antibiotic producing Tn5 mutant of Pseudomonas fluorescens inoculated onto pea plants planted in undisturbed grassland soil containing extensive mycelial networks of arbuscular mycorrhizae associated with the old grass roots.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the finding of Wu et al (2010a) in Citrus tangerine colonized by G. mosseae. On the other hand, root mycorrhizal symbiosis could change the allocation of plant carbohydrates (Pang and Paul, 1980). Typically, AMF need to consume hexose Tab.…”
Section: Carbohydratesmentioning
confidence: 99%